A simple and reliable method to estimate platelet counts that will help in an emergency - Dr. Muthu sudalaimuthu; Dr. Shivashekar Ganapathy; Dr. Koshalya Rajendran (Tropical Journal of Pathology and Microbiology, 1970)
Background: Platelet counts can decrease suddenly in various disorders which need to be diagnosed and managed as early as possible to prevent life-threatening bleeding. Although various methods to estimate platelet counts have been described in the literature, study on platelet count estimation from unstained peripheral blood smears has been mentioned only once in the literature, that too only recently. Considering the potential usefulness of this technique in an emergency, we aimed to estimate the platelet counts from unstained peripheral blood smears and compared it with results from stained smears.Materials and Methods: Platelet counts were estimated in 200 cases using unstained peripheral smears by observing them under oil immersion objective with a lowered condenser and closed iris diaphragm. Platelets were counted in ten oil immersion fields and their average was multiplied by 15000. The same smears were stained and platelet counts determined by routine method. Student’s t test was used to compare the results of two methods.Results: Platelet counts obtained from unstained peripheral smears were not significantly different from stained smears (p value of 0.243). Although platelet counts were underestimated in 75% cases, the maximum deviation was only 15000 in cases of thrombocytopenia and 30000 in patients with normal platelet counts.Conclusion: Platelet counts from unstained peripheral blood smears yield results similar to stained peripheral smears. It can be used in an emergency situation when the routine laboratory facilities are not available and when the treating clinician wants to gain early vital information.